Κατασκευαστικές λεπτομέρειες σε ξύλινη οικοδομή - Νεοφύτου, Δέσπω (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
As the title of the thesis point out the purpose of this dissertation is to present the detailing in timber structures. The following effort to do that shows the points that must take in concern for a timber building in order to be efficient. At first the timber structure is being appeared along with the wood as a material in general. Subsequently the details are being classification by the way the members are been placed in place and the parts of a timber building and especially as it concern the foundation, the flooring, the roof and the walls. The following chapters are about ventilation to prevent moisture in the structure, as well as the appliances. Finally the last part is some conclusions I made during my research.
Keywords: Wood; Wooden building; Moisture; Ξύλο; Ξύλινη οικοδομή; Υγρασία